Optimization to Raise Awareness of Paying Zakat through Accountability and Quality of Service AsModeration Variables - Mahyudin; Irfan; Widia Astuty (Publisher Cv. Inara, 2020)
The purpose in this study is 1) to know the effect of accountability on the awareness of muzakki paying zakat. 2) To know the effect of the quality of service on the quality of service affects the awareness of muzakki paying zakat. 3) To know the effect of the quality of service moderating the effect of ability on the awareness of musakki paying zakat Data analysis techniques using the Partial Least Squart (PLS) based Structure Equation Model (SEM) method of SmartPls software version 3 for windows. The result of accountability is affected by the awareness of muzakki paying zakat the better and the better the quality of service will increase the awareness of muzakki in paying zakat to the zakat management institution. For management of zakat institution is always pay attention to the accountability of zakat management because it has a significant effect on the awareness of paying zakat, for researchers who want to continue this research to pay attention to variables and populations in this study in order to be developed.